2007
DOI: 10.1037/0022-3514.92.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Parental Personality as an Inner Resource That Moderates the Impact of Ecological Adversity on Parenting.

Abstract: Parents' personality was examined as a moderator of the impact of demographic risk on parenting in a longitudinal study (N=102 families). Parents' personality and demographic risk (i.e., education level, age, family income, and family size) were assessed when children were infants, and parents' power assertion, warmth, and positive affect were observed in naturalistic interactions 2.5 years later. Parents' personality moderated the adverse impact of demographic risk on parenting. For parents who had memories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 61 publications
1
20
0
2
Order By: Relevance
“…As a result, finding associations between parenting behaviors and contextual sources of stress might not be expected. The associations found in this sample extend other recent associations found between contextual demographic factors and individual differences observed in maternal parenting in low-risk samples (Kochanska et al, 2007;Popp et al, 2008). The present findings demonstrate that the associations were found even when multiple determinants of parenting were considered.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As a result, finding associations between parenting behaviors and contextual sources of stress might not be expected. The associations found in this sample extend other recent associations found between contextual demographic factors and individual differences observed in maternal parenting in low-risk samples (Kochanska et al, 2007;Popp et al, 2008). The present findings demonstrate that the associations were found even when multiple determinants of parenting were considered.…”
Section: Discussionsupporting
confidence: 87%
“…In two recent studies (Kochanska, Aksan, Penney, & Boldt, 2007;Popp, Spinrad, & Smith, 2008), negative relations between contextual demographic risk factors and optimal parenting behaviors have been found in predominantly homogenous middle-class samples of parents of toddlers. Because parenting behaviors can be negatively associated with increased contextual risk even in low-risk parents, how contextual sources of stress and support are associated with parenting behaviors should not be limited to high-risk samples.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…Those constructs were coded, by independent groups of coders, in multiple naturalistic, carefully scripted, developmentally appropriate contexts that had been designed to elicit a variety of emotions, behaviors, and interactions within the dyad (e.g., parent is busy while child has free time, snack time, parent and child play with toys or complete a craft project, child cleans up toys, parent and child open gifts together). Notably, all of the reported coding systems have been used extensively in our laboratory including the systems for the parent’s and the child’s expressed affect (e.g., Kochanska et al 2007), parent–child MRO (e.g., Kochanska et al 2013), and the parent’s power assertion (e.g., Kochanska et al 2008). Overall, each parent–child dyad was coded in 185 min over the repeated assessments (65, 60, and 60 at 4.5, 5.5, and 6.5 years).…”
Section: Methodsmentioning
confidence: 99%
“…Fathers higher in Openness were more responsive, whereas those higher in Extraversion were less consistent in tracking. Kochanska, Aksam, Penny, and Boldt (2007) found that parental personality is a moderator of the effects of demographic adversity. In a longitudinal study of 102 community families, demographic risk (larger family size and lower education level, family income, and age) was associated with greater parental assertion of power, but only for fathers higher in Neuroticism and for mothers lower in Extraversion.…”
Section: The Ffm and Parentingmentioning
confidence: 99%
“…For example, high Conscientiousness and high Agreeableness both appear to be related to positive child outcomes, but for a particular child, high parental Conscientiousness might be more important than high Agreeableness, or vice versa. Some investigators have attempted to look at interactions between parent personality and child characteristics such as temperament (e.g., Kochanska et al, 2007;Mangelsdorf, Gunnar, Kastenbaum, Lang, & Andreas, 1990), but results are not broadly established. Finally, the FFM parenting literature implicitly defines parenting in terms of direct parent-child interactions and has little to say about the role of personality in other areas that may nevertheless affect children.…”
Section: The Ffm and Parentingmentioning
confidence: 99%